LEFT SIDED MORGAGANI HERNIA WITH VOLVULUS OF STOMACH: Morgagni Hernia with Volvulus of Stomach - Abbas, Capt Ghulam; Majeed, Farhan Ahmed; Nafees, Muhammad (Pakistan Armed Forces Medical Journal, 2010)
Morgagni hernia is a congenital herniation of abdominal contents into the thoracic cavity through a retrosternal diaphragmatic defect. It was first described by Morgagni in 17901. The reported incidence of congenital diaphragmatic hernias is estimated to be 1 in between 2000 to 5000 births. They are usually asymptomatic and often found incidentally on chest radiography. Although it is generally diagnosed incidentally by chest X-Rays, it rarely become complicated and may lead to severe disturbances. Symptoms of these hernias are attributable to the herniated viscera2. Intestinal obstruction is caused by a strangulated Morgagni hernia in an adult patient. Most Morgagni hernias are found and repaired in children, but 5% are found in adults. By presenting this case we aim to discuss an unusual left sided Morgagni hernia with gastric volvulus.